Ozone in Medicine: A Few Points of Reflections - Re, Lamberto (Frontiers in Physiology, 2022)
Notwithstanding the use of ozone in medicine has become widespread in many countries of the world, its real pharmacological action remains not completely clarified. We know that other than its uses as disinfectant, well documented by the literature since the beginning of the past century, the more recent medical use of ozone in several pathologies as described by the international literature is still poor investigated. Furthermore, following its clinical uses with excellent clinical responses on several heterogeneous diseases and pain, it is now clear that the biological activity of this gas is mediated by graded responses to the mild oxidative stress induced after its application. Thus, the ancestral environment of our cells, whose energy production is strictly bind to oxygen burn, may be mediated by common defenses probably linked to the ubiquitous signaling pathway mediated by Nrf2. Moreover, after the first description of the oxidative stress in the 1970s and the discovery of Nrf2 as transcription factor in 1994, we could observe a rapid growth of the literatures regarding its function as master regulator of a myriad of cellular processes and its association to a multiple pattern of diseases including aging. In conclusion, to our opinion, the Systems Medicine approach could finally give to us the real key to better understand the wide reported efficacy of ozone treatment.